2010
DOI: 10.1245/s10434-010-1084-2
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Quality of Surveillance after Curative Surgery for Colon Cancer

Abstract: The quality of surveillance after curative surgery for colon cancer among a cohort of Swiss patients is inadequate. Further education of health care professionals and patients regarding the potential life-saving benefits of surveillance is imperative. It is cardinal that quality of surveillance is critically analyzed in other countries with different health care systems as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…this data confirms what was only implicit in the swiss study. those authors, in fact, reported that the patients had a low adherence to postoperative surveillance programs, but they did not attempt to correlate this data to the actual curability of the recurrence (25). our results suggest, instead, that improved survival might be due to the diagnosis of recurrence formulated at an early, asymptomatic stage when the tumor was still treatable and could be operated on successfully.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…this data confirms what was only implicit in the swiss study. those authors, in fact, reported that the patients had a low adherence to postoperative surveillance programs, but they did not attempt to correlate this data to the actual curability of the recurrence (25). our results suggest, instead, that improved survival might be due to the diagnosis of recurrence formulated at an early, asymptomatic stage when the tumor was still treatable and could be operated on successfully.…”
Section: Discussionmentioning
confidence: 61%
“…Modern neadjuvant chemotherapy regimens in addition to biologic agents can potentially downstage resectable liver metastases, and as high as a 50% 5-year survival rate can be achieved with radical resection (23,24). as underlined by a recent swiss study, reticence about the treatment of colorectal cancer recurrence is no longer justified since surveillance programs have proved increasingly effective (25). those same authors commented nevertheless that even when universally accessible, as in the case of the swiss health care system, surveillance after curative surgery for colon cancer is often inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Overall patientreported satisfaction was assessed in terms of satisfaction with bowel, stoma, and urinary function on a 4-point scale (very good, Clinical Colorectal Cancer September 2017 -241 good, poor, very poor); (3) Adherence to National Guidelines: modality and frequency of all performed follow-up examinations were recorded and compared with the Swiss Society of Gastroenterology guidelines (www.sggssg.ch). 16,17 PFS and OS curves were calculated according to the Kaplan-Meier method for all patients. Exploratory subgroup analyses were preplanned for the following factors (groups, yes/no): tumor downstaging (T-stage), nodal downstaging (N-status), complete histopathologic response to neoadjuvant treatment (Dvorak regression grade 3 or 4), and grade 3 or 4 diarrhea or lymphopenia during neoadjuvant treatment and adjuvant chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…The Swiss societies for gastroenterology and visceral surgery published consensus recommendations for aftercare after curatively operated colorectal carcinoma [3]. Studies showed that the quality of surveillance after curative surgery for colon cancer among a cohort of Swiss patients is inadequate [4]. One reason is that it is still challenging for patients to remember their appointments and there is no other reminder system in place that could help.…”
Section: Introductionmentioning
confidence: 99%
“…One reason is that it is still challenging for patients to remember their appointments and there is no other reminder system in place that could help. Viehl state that "further education of health care professionals and patients regarding the potential life-saving benefits of surveillance is imperative" [4]. We believe that mHealth has the potential of improving this situation.…”
Section: Introductionmentioning
confidence: 99%